2017
DOI: 10.1097/sla.0000000000001991
|View full text |Cite
|
Sign up to set email alerts
|

To Drain or Not to Drain Infraperitoneal Anastomosis After Rectal Excision for Cancer

Abstract: This randomized trial suggests that the use of a pelvic drain after rectal excision for rectal cancer did not confer any benefit to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
92
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 24 publications
13
92
2
1
Order By: Relevance
“…Six further studies were identified through hand searching of references. After the evaluation of full-texts, 4 studies [12, 13, 19, 20] eventually met all the inclusion criteria and were included in the meta-analysis. The flow diagram in Figure 1 describes the selection process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six further studies were identified through hand searching of references. After the evaluation of full-texts, 4 studies [12, 13, 19, 20] eventually met all the inclusion criteria and were included in the meta-analysis. The flow diagram in Figure 1 describes the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Three [12, 13, 20] of the included studies were from Europe and one from Asia [19]. Three studies included only patients with extraperitoneal anastomoses [12, 13, 19], whereas the other RCT [20] referred to any type of anastomosis following rectal surgery but provided specific data concerning the group of patients with extraperitoneal anastomosis (132 patients out of 494).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations